The nurse's effective communication process with the patient in palliative care (Research, Society and Development, 2020)
Communication is the verbal language whose basic unit is the word (spoken and written) and non-verbal as gestures, music, dance, image, among others. This article aimed to study the role of nurses in effective communication in patients in palliative care. The objective was to identify in the literature the importance of effective and affective communication in nursing care for patients in palliative care. It is an integrative literature review of a qualitative nature whose analysis was an exploratory approach. The results showed the scarcity of specific studies about the process of effective communication between nurses and patients in palliative care. After exploring the material, two categories emerged: Effective communication process as an essential tool for nursing care and feelings and emotions evidenced by nurses in the patient's communication process in palliative care. We conclude that communication works as a tool in the process of easing anxiety, depression, fear, anger, among other confused feelings when their clinical health condition is revealed and serves to clarify this period of doubt. Becoming one of the main skills in the nursing care process.